Precursor Design Strategies for the Low‐Temperature Synthesis of Functional Oxides: It's All in the Chemistry. Issue 42 (17th April 2020) - Marchal, Wouter; De Sloovere, Dries; Daenen, Michael; Van Bael, Marlies K.; Hardy, An
Abstract: Solution‐based (multi)metal oxide synthesis has been carried out employing a large diversity of precursor routes. The selection of an appropriate synthesis strategy is frequently dictated by the resulting material properties, although this choice should also be based on green chemistry principles, atom economy considerations and energy efficiency. In order to limit the required energy budget to convert the chemical precursor to the target oxide material, various approaches were recently reported. This Review summarizes some frequently encountered low‐temperature routes, critically assessing their application window and advantages. More specifically, auto‐combustion synthesis, UV‐assisted decomposition routes, sol–gel network adjustments and precursor complex design concepts are discussed. It is expected that this toolbox of low‐temperature strategies may assist further progress in the field, stimulating novel applications, such as flexible electronics or organic–oxide hybrid materials, which are very sensitive to the temperature requirements. Abstract : Overview of the different explored low‐temperature strategies increasing the energy efficiency for functional oxide synthesis, taking into account the application of green precursors and atom economy considerations.